Pembelajaran Sintaksis Menggunakan Metode Sinkronus dan Asinkronus: Manakah Yang Lebih Baik? - Ramadhanti, Dina; Yanda, Diyan Permata (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2025)
Syntax is one of the courses taken by students either in the form of online learning using e-learning or face-to-face in the classroom. In online learning using e-learning, syntax is taught using asynchronous and synchronous methods. This study aims to explain which online learning method is more appropriate to use in learning syntax. This research method uses an experimental design. A total of 80 students received syntax learning with the asynchronous method in the first half of the semester and the synchronous method in the second half of the semester. The results of the study showed three things, namely: the average learning outcome with the asynchronous method was 52.79, the average learning outcome with the synchronous method was 63.34, and the results of statistical tests showed that there was a significant difference between learning outcomes using the asynchronous and synchronous methods. The synchronous method is better than the asynchronous method because online learning is carried out directly using the zoom meeting virtual room. Lecturers and students interact directly in the virtual room so that students have the same understanding in understanding and applying the concepts of Syntax learning, both in oral and written communication. Although learning can be carried out, the average student grades still need to be improved. Lecturers need to improve the quality of learning. Meanwhile, students need to improve their motivation, reading interest, and be able to adapt to various forms of learning in various situations